The Anthropocene: a new frame of studies and its limits - Ana Carolina Lins Peliz (Esboços, 2021)
This article is a commentary on an article by Patrícia Vieira published in the current issue of Esboços: histórias em contextos globais, in which the author discusses the thesis that the idea of the annihilation of humanity could be read through the optic of a utopian perspective and not only from a dystopian view in the age of the Anthropocene. She uses the trilogy of the Canadian writer Margaret Atwood, MaddAddam, as an example of her central idea. The theoretical framework is structured around an interdisciplinary study of authors from political sciences, history, sociology and literature. This work is organized in two parts: the first summarizes the main ideas in Vieira’s article, and the second proposes a debate about the concept of Anthropocene, its limits and difficulties regarding human and social sciences.